Sexual Harassment Reflected At Nawal El Saadawi 'S Women At Point Zero (1983): A Feminist Approach - Padang Rahayu, Harsiti Helen, Dr. Phil dewi Chandraningrum, Titis Setyabudi, S.S. M. Hum (2015)
The major problem of this study is to reveal how the major character shows her sexual harassment. The objectives of this study are to analyze the novel based on its structural elements and on the feminist analysis. The research uses qualitative research. The data of the research consists of primary data and secondary data. The primary data of the research is the Women at Point Zero novel and the secondary data of the research are other materials related to the study. The result of the study shows the following conclusion. Based on the feminist analysis, Nawal El Sadaawi illustrated how a woman is able patriarchal culture, Firdaus as prostitution in the society. It is based on the reality in daily long-life story that women as Firdaus. In this reality this condition women in Mubarak Era, a women feels condition and situation patriarchal culture in Egypt. Women at Point Zero is a true novel Condition in situation patriarchal culture in Egypt. Feminist Perspective, Feminist is a concept that is against all of the dominance of men toward women.